An exploratory examination of practitioners' and offenders' perceptions of the effectiveness of an individual workbook approach for treating intimate partner violence offenders. Issue 10 (25th November 2016) - Walker, Kate; Brown, Sarah; Hicks, Katy
ABSTRACT: Perceptions of probation staff and offenders were explored regarding the effectiveness of an individual workbook intervention for intimate partner violence (IPV), based on the Integrated Domestic Abuse Programme, a group intervention for IPV offenders in the UK. Using thematic analysis, interview transcripts from 11 probation staff and 2 offenders were examined. Two global themes were identified: Promising alternative to IPV interventions, representing positive perceptions of the workbook and Compromises made in using the workbook, reflecting negative perceptions and challenges. The identified strengths were that the workbook provided staff with a framework to deliver individualised intervention (deemed to be more difficult in group treatment formats), employed a strength-based and directive approach to discussions to develop offenders' skills and behaviours that may assist in improving deficits linked to their use of violence. However, identified problematic factors related to treatment integrity including delivery, content and format, its capacity to create change, and a need for further development. As a concept the workbook intervention should not be discounted since it offers an opportunity to offer individualised treatment and interventions to those unable to attend groups; however, the intervention requires development and further research to examine its effectiveness.